Development of mycobacterium tuberculosis 16 kDa protein detection using immunochromatography test - Mohd Nawi, Mohd Amiruddin (2015)
Mycobacterium tuberculosis (Mtb) is a pathogenic bacterium that can cause tuberculosis (TB). This contagious disease remains a severe health problem in the world. The disease is transmitted via inhalation of airborne droplets carrying Mtb from TB patients. Early detection of infection is vital to prevent transmission of the disease to people in close contact with the patients. To date, there is no simple, rapid, sensitive and specific diagnostic test for TB. Previous studies showed the potential of Mtb 16 kDa antigen in TB diagnosis. In this study, an immunochromatographic (ICT) lateral flow dipstick assay against 16 kDa antigen was developed and assessed as a potential rapid method to diagnose TB. A 16 kDa monoclonal antibody was optimized as the capturing and detection antibody on the ICT platform. The parameters of control line, blocking reagent, running buffer, conjugate and sample pad were also optimized before a complete prototype of TB-antigen ICT dipstick was developed. Sensitivity studies on TB-antigen ICT prototype dipstick showed that the dipstick was capable to detect purified 16 kDa antigen as low as 125 ng. However, the specificity of the assay was inconclusive probably due to the method used for sample preparation, which needs further study. The analytical sensitivity suggests its potential usefulness in different clinical applications.